Sous le talent : la classe, le genre, la race - Buscatto, Marie; Cordier, Marine; Laillier, Joël (Éditions Agone, 2020)
Le paradoxe des écoles d’art est de se présenter comme des lieux d’apprentissage de ce qui ne s’apprend pas : le “talent” est ce que l’on possède à titre personnel. Et ce alors même que l’accès à la formation artistique est aujourd’hui un élément clé dans la construction des trajectoires professionnelles des artistes. Une vision courante de ces écoles est ainsi qu’elles se contentent de faire éclore les “talents” qu’elles repèrent, nourrissent et accompagnent. Prenant le contre-pied de cette conception individuelle de la réussite, ce volume montre que la classe sociale, le genre ou la « race » sont décisifs à l’entrée dans les formations comme au fil de la scolarité ou à sa sortie. À travers l’étude de multiples arts — cirque, théâtre, arts visuels, mode, musique et photographie — sont montrées les différentes manières dont les formations artistiques participent à la construction invisible et “naturelle” de ces inégalités qui se répercutent ensuite en profondeur dans les univers artistiques eux-mêmes.
https://shs.hal.science/halshs-03246295
Keywords: allemagne; approches et analyses; arts; cirque; danse; discipline; europe; france; histoire; mode; photographie; racisme; royaume-uni; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail

Polyrhythmic dance currents: Race multiculturalism and the montreal dance community - Templeton, Melissa (Université de Californie à Riverside, 2012)
This dissertation examines African and African Diaspora concert dance in Montreal in relation to Canadian multicultural policies and Québec nationalism. The multiple layers of colonization and various waves of immigration to Québec have made the province a unique nation with its own complex history of racial construction, quite unlike the racial histories of the U.S. or the rest of Canada (though still greatly informed by these racial paradigms). In the debates that arise in Québec over multiculturalism, language is often seen as the main cultural component in need of preservation. However, this focus on language often masks other elements at play in these cultural debates, in particular, how "race" informs notions of cultural belonging in Québec. A focus on African Diaspora dance in Montreal (Québec's largest and most demographically varied city) helps bring racial construction to the fore for two reasons. First, language differences do not distinguish Québec's Black community from the white French-Canadian majority as Québec's Black population is comprised mainly of French-speakers, and accordingly, studying Montreal's African Diaspora reduces the significance of linguistic difference. Second, concentrating on dance practices helps identify how the Montreal public interprets bodies and their cultural meanings. By analyzing the public support and critical reception of African Diaspora dance practices in Montreal, this dissertation examines how racial difference is constructed through multicultural rhetoric, policies, and debates about dance; it also suggests that dance practitioners have the ability to change and inform these constructed identities and the social landscape that frames them. To conduct this research, I use archival material along with personal interviews and participant-observer ethnography to examine: the early visits of Les Ballets Africains to North America (with a particular focus on Montreal); the Montreal-based company Les Ballets Jazz; the 1999 Montreal festival Afrique: Aller/Retour; and the work of Contemporary African dance choreographer Zab Maboungou. With these subjects, my projects contributes a partial history of African Diaspora dance in Montreal and analyzes the effectiveness and the shortcomings of Canadian Multiculturalism on this community.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; danse; diaspora africaine; discipline; montréal; multiculturalisme; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques